2000
DOI: 10.1002/1097-0223(200009)20:9<758::aid-pd899>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to prenatal treatment of extralobar pulmonary sequestration

Abstract: Fetal hydrothorax and hydrops is a frequent complication of extralobar pulmonary sequestration which is associated with a high perinatal mortality and severe respiratory insufficiency in the newborn. In a 27‐week‐old fetus with this condition, injection of 1 ml of pure alcohol and pleuro‐amniotic shunting achieved resolution of hydrops. The pregnancy progressed to term and a healthy neonate was delivered who did not require postnatal surgery. Copyright © 2000 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 12 publications
0
34
0
3
Order By: Relevance
“…A spiral CT with contrast angiography and magnetic resonance imaging (MRI) are the diagnostic techniques of choice [5,7,11,[19][20][21][22][23][24][25][26] . The treatment of an extralobar sequestrum is mainly by surgical excision which removes the mass completely total of the sequestrum to reduce the risk of repeated infection [2,5,7,19,20,[27][28][29] . To the best of our knowledge, this study is the first reported case of extralobar pulmonary sequestration in a mixed-breed dog that describes.…”
Section: Discussionmentioning
confidence: 99%
“…A spiral CT with contrast angiography and magnetic resonance imaging (MRI) are the diagnostic techniques of choice [5,7,11,[19][20][21][22][23][24][25][26] . The treatment of an extralobar sequestrum is mainly by surgical excision which removes the mass completely total of the sequestrum to reduce the risk of repeated infection [2,5,7,19,20,[27][28][29] . To the best of our knowledge, this study is the first reported case of extralobar pulmonary sequestration in a mixed-breed dog that describes.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis is poor in cases diagnosed before 26 weeks' gestation and is associated with mediastinal shift, polyhydramnios and fetal hydrops 4,5 . Prenatal management of complicated BPS has included treatment with direct fetal furosemide and digoxin therapy 6 , thoraco-amniotic shunting 7,8 and combined absolute alcohol injection into the feeding vessel and placement of a thoraco-amniotic shunt 9 . Open fetal surgery with resection of an extralobar BPS has also been reported 8 .…”
Section: Discussionmentioning
confidence: 99%
“…It carries additional maternal surgical risks and creates a uterine scar. Doppler ultrasound guided fetoscopic laser vessel ablation is a minimally invasive alternative, with survival rates in excess of 87.5% [101,103]; sclerosants injected into the aberrant vessel have shown high success rates, but trials have small numbers [104,105]. Complication rates are not quoted.…”
Section: Bronchopulmonary Sequestrationmentioning
confidence: 99%